Redox Remodeling by Nutraceuticals for Prevention and Treatment of Acute and Chronic Inflammation - Claudia Petrarca; Davide Viola (MDPI AG, 2023)
Antioxidant-rich dietary regimens are considered the best practice to maintain health, control inflammation, and prevent inflammatory diseases. Yet, nutraceuticals as food supplements are self-prescribed and purchasable over the counter by healthy individuals for the purpose of beneficial effects on fitness and aging. Hence, the effectiveness, safety, and correct intake of these compounds need to be better explored. Since redox-modulating activity of these compounds appears to be involved in activation and or suppression of immune cells, the preventive use of nutraceuticals is very attractive even for healthy people. This review focuses on redox- and immunomodulating nutraceuticals in the context of diabetes mellitus (DM). In fact, DM is an illustrative disease of latent and predictable inflammatory pathogenetic processes set out and sustained by oxidative stress. DM has been thoroughly investigated through in vitro and in vivo models. Furthermore, human DM is characterized by uncontrolled levels of glucose, a pivotal factor shaping immune responses. Hence, antioxidant nutraceuticals with multifaced activities, including glucose keeping, are described here. A greater number of such multi-player nutraceuticals might be identified using DM animal models and validated in clinical settings on genetic and environmental high-risk individuals.